In love's time [large type] - Breslin, Kate (Thorndike Press large print Christian romance series., 2023)
"In the summer of 1918, Captain Marcus Weatherford arrives in Russia on a secret mission, with a beautiful ballerina posing as his fiancée. Marcus searches for the Romanov tsarina and her son--who both allegedly survived the murdering Bolsheviks--and the information behind an allied plot to assassinate Lenin. But Marcus's sense of duty battles his desire to return home to Clare--his actual love.Hospital orderly Clare Danner still suffers from Marcus's betrayal and now fears losing her daughter to the heartless family who took Daisy away from Clare once before, but only Marcus can provide the critical proof needed to save her daughter. Faced with danger and unexpected circumstances, can Clare trust Marcus, or will he shatter her world yet again?"--